Inequality in health opportunities in Indonesia: long-term influence of early-life circumstances on health - Toshiaki Aizawa (BMC, 2022)
Abstract Background This study explores inequality of opportunity in terms of the health of adult Indonesian people, associated with household and parental circumstances in childhood and adolescence. Methods Exploiting the longitudinal nature of the Indonesian Family Life Survey, this study measures inequalities relating to being underweight, overweight, hypertensive and diabetic across adult Indonesians aged between 20 and 35 through the dissimilarity index. This study explores their determinants by decomposing the observed inequality levels into contributing factors. Moreover, this study sheds light on the underlying mechanisms through which early-life circumstances influence the health of grown-up respondents, by estimating the intermediate effects of early-life circumstances on current lifestyles. Results For all health conditions, health risks are unequally distributed (all p<0.01). Demographic factors and parental health are major contributors to inequalities relating to being underweight, overweight and hypertensive. Family structure and parental occupation are major contributors to inequality in diabetes. The greater part of this inequality is explained by the indirect pathways through which early-life circumstances mediate current diet and exercise habits. Conclusions The results suggest that such interventions that compensate for disadvantaged early-life circumstances would be essential in reducing future health risks and mitigating health inequality.